Soil Organic Matter in Sustainable Agriculture - Magdoff, Fred (CRC Press, 2009)
Read it Online! Recognition of the importance of soil organic matter (SOM) in soil health and quality is a major part of fostering a holistic, preventive approach to agricultural management. Students in agronomy, horticulture, and soil science need a textbook that emphasizes strategies for using SOM management in the prevention of chemical, biological, and physical problems.